The effect of child benefit on female labor supply - Iga Magda; Aneta Kiełczewska; Nicola Brandt (IZA Journal of Labor Policy, 2020)
In 2016, the Polish government introduced a large child benefit, called "Family 500+", with the aim to increase fertility and reduce child poverty. It is universal for the second and every further child and means-tested for the first child. We study the impact of the new benefit on female labor supply, using Labor Force Survey data. Based on a difference-in-differences methodology, we find that the labor market participation rates of women with children decreased after the introduction of the benefit compared to that of childless women. The labor force participation rate of mothers showed a drop of 2-3 percentage points by mid-2017 as a result of the "Family 500+" program. The effect was higher among women with lower levels of education and among women living in small towns.
Keywords: E24; H53; I38; J13; J21; J22; 330; child allowance; social transfers; family policy; labor market participation